Changements côtiers et inondations suite au passage d’un ouragan extrême (Irma, 2017) aux Petites Antilles - Tony Rey; Thomas Candela; Matthieu Péroche; Frédéric Leone (EchoGéo)
This study deals with the coastal changes, flooding and damage after the passage of a category 5 hurricane (Irma) on 6 September 2017 over the islands of Saint-Martin and Saint-Barthélemy in the Lesser Antilles. Two field work were made 2 and 8 months after the catastrophe over the two islands. It made it possible to analyze the impacts of Hurricane Irma on the low-lying shores that are particularly susceptible to extreme cyclonic events and anthropogenic stressors. The field work was made on the coasts most affected by the cyclonic event. To compare impacts of hurricane Irma and interactions with coastal systems and coastal infrastructure, we chose to analyze undeveloped to highly urbanized coasts. The method was based on the analysis of satellite images and Unmanned Aerial Vehicle surveys. It also relied on qualitative observations, geomorphological and sedimentary surveys and the measurement of wave run up and the mapping of flooded areas. The coastal system revealed a variety of morpho-sedimentary responses on both the natural and highly urbanized coasts, showing varied coastal changes, perturbed sedimentary transfers and the effects of coastal structures and street on flow channeling and on water level increase